2006
DOI: 10.2134/jeq2005.0144
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire Effects on Soil Nutrients and Leaching in a Tahoe Basin Watershed

Abstract: A wildfire burned through a previously sampled research site, allowing pre- and post-burn measurements of the forest floor, soils, and soil leaching near Lake Tahoe, Nevada. Fire and post-fire erosion caused large and statistically significant (P < or = 0.05) losses of C, N, P, S, Ca, and Mg from the forest floor. There were no statistically significant effects on mineral soils aside from a decrease in total N in the surface (A11) horizon, an increase in pH in the A11 horizon, and increases in water-extractabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 35 publications
11
97
2
Order By: Relevance
“…These materials were then segregated into: 1) litter (the surface layer which is not in an advanced stage of decomposition, typically consisting of freshly fallen and dried leaves, needles, twigs, stems, bark, and fruits; 2) duff (the layer dominated by partially to fully decaying leaves and branches); and 3) topsoil (mixture of mineral soil, humus, and/or degraded organic material). Topsoil was examined because Murphy et al (2006) found that wild fires nearly deplete C and N in soils. Common aboveground shrubs were also collected and separated in the laboratory into leaves and stems of different diameters.…”
Section: Methodsmentioning
confidence: 99%
“…These materials were then segregated into: 1) litter (the surface layer which is not in an advanced stage of decomposition, typically consisting of freshly fallen and dried leaves, needles, twigs, stems, bark, and fruits; 2) duff (the layer dominated by partially to fully decaying leaves and branches); and 3) topsoil (mixture of mineral soil, humus, and/or degraded organic material). Topsoil was examined because Murphy et al (2006) found that wild fires nearly deplete C and N in soils. Common aboveground shrubs were also collected and separated in the laboratory into leaves and stems of different diameters.…”
Section: Methodsmentioning
confidence: 99%
“…Wildfire was found to induce an immediate mobilization of inorganic N and P [53]. Although small compared to volatilization losses, N leaching fluxes ( Figure 5A) from resin lysimeter measurements demonstrated significant (p < 0.05) increases 2 years post fire, with a shift from NH 4 + to NO 3 − (nitrite + nitrate) N between post burn years 1 and 2 [53][54] and a sharp decline in year 3.…”
Section: Effects Of Wildfirementioning
confidence: 95%
“…Although small compared to volatilization losses, N leaching fluxes ( Figure 5A) from resin lysimeter measurements demonstrated significant (p < 0.05) increases 2 years post fire, with a shift from NH 4 + to NO 3 − (nitrite + nitrate) N between post burn years 1 and 2 [53][54] and a sharp decline in year 3. On the other hand, P leaching fluxes ( Figure 5B) showed no immediate change post burn, but a significant (p < 0.10) increase in post burn year 2.…”
Section: Effects Of Wildfirementioning
confidence: 95%
See 1 more Smart Citation
“…Direct measurements of pre-and post-wildfire samples render assumptions concerning pre-fire conditions unnecessary. Studies in which soil C measurements are available before and after wildfires are rare and lack mention of the presence or absence of charcoal [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%